Citrullinated histone H3 in systemic lupus erythematosus and antiphospholipid syndrome (preliminary results) - K. S. Nurbaeva; T. M. Reshetnyak; M. V. Cherkasova; A. M. Lila (Современная ревматология, 2023)
Citrullinated histone H3 (CitH3) is a specific marker for NETosis; its role in determining the clinical and laboratory manifestations of systemic lupus erythematosus (SLE) remains to be elucidated.Objective: To evaluate the role of CitH3 in the development of clinical and laboratory manifestations in patients with SLE with and without an-tiphospholipid syndrome (APS).Material and methods. The study included 30 patients with SLE and 39 with SLE+APS, including 51 (73.9%) women and 18 (26.1%) men. The median age of the patients was 36 [32; 46.5] years. The control group consisted of 26 healthy individuals.SLE activity was assessed by the SLEDAI-2K index. Patients were divided into two groups: 41 patients with moderate and high SLE activity (SLEDAI-2K ≥6) were included in the first group, and 28 patients with low activity or remission (SLEDAI-2K <6) were included in the second group.CitH3 content in blood serum was determined by enzyme immunoassay using a set of reagents for the assay of CitH3 (BlueGene Biotech, China) according to the manufacturer's instructions.Results and discussion. CitH3 content in blood serum was significantly higher in SLE than in the control group (p=0.048). High blood serum CitH3 content was associated with moderate and high SLE activity (p=0.039). CitH3 concentration was inversely correlated with lymphocyte count but was not related to immunological parameters. Increased CitH3 levels were associated with photosensitivity, while lower levels were associated with a history of serositis. There were no significant differences between blood serum CitH3 levels in patients with SLE and SLE+APS (p=0.39).Conclusion. The concentration of a specific marker for NETosis, CitH3, is increased in patients with SLE, and this increase is associated with moderate and high disease activity.